Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2020
DOI: 10.1155/2020/6096391
|View full text |Cite
|
Sign up to set email alerts
|

Dihydroartemisinin Modulates Apoptosis and Autophagy in Multiple Myeloma through the P38/MAPK and Wnt/β-Catenin Signaling Pathways

Abstract: Dihydroartemisinin (DHA), an active metabolite and derivative of artemisinin, is the most effective antimalarial drug and has strong antitumor activity in various tumor types. It has recently been reported that DHA can induce autophagy and has significant effects on multiple myeloma (MM), but the mechanisms and the relationship between the autophagy and apoptosis induced by DHA remain to be elucidated. Herein, we demonstrated that DHA significantly induces cell death in a dose- and time-dependent manner via th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
23
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(29 citation statements)
references
References 40 publications
2
23
0
Order By: Relevance
“…We also revealed the mechanism underlying BRG1/Wnt/β-catenin axis in inducing tubular senescence could be related to the inhibition of autophagy. Previous studies have provided evidence that Wnt/β-catenin signalling acts as a crucial negative regulator of autophagy activation [86][87][88]. In line with these findings, we observed that the inhibition of Wnt/β-catenin pathway by ICG-001 reversed BRG1-mediated autophagy suppression, suggesting that BRG1 inhibited autophagy through activating Wnt/β-catenin signalling.…”
Section: Discussionsupporting
confidence: 91%
“…We also revealed the mechanism underlying BRG1/Wnt/β-catenin axis in inducing tubular senescence could be related to the inhibition of autophagy. Previous studies have provided evidence that Wnt/β-catenin signalling acts as a crucial negative regulator of autophagy activation [86][87][88]. In line with these findings, we observed that the inhibition of Wnt/β-catenin pathway by ICG-001 reversed BRG1-mediated autophagy suppression, suggesting that BRG1 inhibited autophagy through activating Wnt/β-catenin signalling.…”
Section: Discussionsupporting
confidence: 91%
“…Here we also found that overexpression of GADD45B could facilitate phosphorylation of p38 under docetaxel treatment. Considering that p38/MAPK pathway is an important upstream of apoptosis (Fang et al, 2020;Wu et al, 2020), we suggest that GADD45B promotes cell apoptosis through p38/MAPK pathway. It should be noted that overexpression of GADD45B itself did not cause cell apoptosis, even though it could activate p38/MAPK.…”
Section: Discussionmentioning
confidence: 88%
“…Many MAPK pathway–related genes were also up-regulated when GADD45B was overexpressed ( Figure 7F ). Considering that p38/MAPK is an important upstream of apoptosis ( Fang et al, 2020 ; Wu et al, 2020 ), GADD45B might regulate apoptosis by activating p38/MAPK pathway, thus facilitating chemotherapy sensitivity. WB was performed, and it was found that p-p38 was upregulated after docetaxel treatment in DU145 cells.…”
Section: Resultsmentioning
confidence: 99%
“…These results indicated that DHA was a safe potential antitumor reagent with low toxicity. Besides the antimalaria activity, DHA has been reported to exhibit significant anticancer activity in a variety of tumors (Dai et al, 2021), including lung cancer (Jiang et al, 2016), ovarian cancer (Li et al, 2018), MM (Wu et al, 2020), and hepatocellular carcinoma (Zou et al, 2019). Previous study demonstrated that inhibition of telomerase activity could reduce the proliferation and migration of esophageal cancer cells (Li et al, 2020).…”
Section: Discussionmentioning
confidence: 99%